2017
DOI: 10.1016/j.ijrobp.2017.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Pericardial Effusion After Chemoradiation Therapy for Locally Advanced Non-Small Cell Lung Cancer

Abstract: Purpose Findings from RTOG 0617 suggested that collateral radiation to the heart may contribute to early death in patients receiving chemoradiation therapy for non-small cell lung cancer (NSCLC); however, reports of cardiac toxicity after thoracic radiation therapy (RT) remain limited. Because pericardial disease is the most common cardiac complication of thoracic RT, we investigated the incidence of and risk factors for pericardial effusion (PCE) in patients enrolled in a phase II, prospective randomized stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 29 publications
(38 reference statements)
1
43
1
Order By: Relevance
“…Time to death (months) However, the present study provides more detailed analysis on cardiac dose and patient outcomes after SBRT in early-stage lung cancer. Interestingly, in our cohort no pericardial effusions were observed, which is commonly observed after radiotherapy for locally advanced lung cancer (14).…”
Section: Survival Probabilitycontrasting
confidence: 45%
See 1 more Smart Citation
“…Time to death (months) However, the present study provides more detailed analysis on cardiac dose and patient outcomes after SBRT in early-stage lung cancer. Interestingly, in our cohort no pericardial effusions were observed, which is commonly observed after radiotherapy for locally advanced lung cancer (14).…”
Section: Survival Probabilitycontrasting
confidence: 45%
“…Recently, interest in cardiac toxicity in lung cancer patients has increased (10). Several studies showed that radiation dose to the heart in stage III lung cancer patients was associated with the development of cardiac events (7,(11)(12)(13)(14)(15) and overall survival (12,14,15). Importantly, RTOG 0617 showed that the heart volume receiving ≥5 and 30 Gy predicted overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas asymptomatic pericardial effusions occur in up to 40.3% of patients after RT, symptomatic pericardial effusions occur only in 0.7% to 6.3%. 4,14,41 Nevertheless, prior work found associations between cardiac doses and mostly asymptomatic pericardial or pleural effusions. 41,42 A few actionable steps may potentially limit cardiotoxicity after RT for inoperable NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…4,14,41 Nevertheless, prior work found associations between cardiac doses and mostly asymptomatic pericardial or pleural effusions. 41,42 A few actionable steps may potentially limit cardiotoxicity after RT for inoperable NSCLC. First, on the basis of a high cardiac event rate among patients receiving mean WH dose 20 Gy (4-year rate, 48.6% in this study and 41% in Wang et al 3 ), a reasonable constraint for routine planning might be to keep mean WH dose <20 Gy, below the current recommendation of 26 Gy by the NCCN.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies focused on the specific cardiac events. Ning et al [ 40 ] investigated the potential risk factors for pericardial effusion which is the most common complication in radiotherapy and they found that HV35 >10% (cutoff volume is 10%), adjuvant chemotherapy, and previous cardiac disease were predictors of pericardial effusion. Wang et al [ 17 ] also discussed 3 types of cardiac events including pericardial events, ischemic events, and arrhythmic events, respectively.…”
Section: Discussionmentioning
confidence: 99%